CHARACTERISTICS OF RAINFALL AND PRECIPITABLE WATER IN THE ANNUAL AND SEMIANNUAL RAINFALL IN THE AREA WITH VARIOUS INTENSITY OF EL NINO (SUMATERA CASE STUDY) - Agus Safril (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
Indonesia has a range of islands in the maritime continent which surrounded by oceans with strong cloud convection. El Nino events at weak, medium, or strong intensity can cause different effects of convection. Based on these conditions, it is necessary to analyze the characteristics of rainfall when El Nino occurred in Sumatra. The analysis was carried out by looking at the percentage of dominant frequency events of Normal (N), Normal (N), and Above Normal (AN) rainfall in El Nino years. The analysis was also carried for the relationship between the content of precipitable water and sea surface temperatures in the Central Pacific (Nino of 3.4 indexes). The results of the analysis show that the effect of El Nino (in the annual rain cycle) is stronger than the region with the semi-annual rain cycle. The annual rain cycle area in the El Nino intensity category is weak, medium, strong (predominantly BN-N rain characteristics). In the semi-annual rainfall cycle (rainfall between N-AN) it is medium (BN-AN), and strong (N-BN). The average composite percentage in the years of EL Nino shows a weak intensity with the average of rain BN between 37-50%, medium (42-53), and strong (42-48%). Whereas in the annual cycle region, the average rainfall characteristics of the BN category are weak (50-58%), moderate (36-56%), and strong (32-60%). Characteristics of different rain characteristics are due to differences in the atmospheric ability to capture moisture. Correlation in the region with the annual rain cycle (June-July-August) between the Nino 3.4 Index and the precipitable water content shows a strong (r) correlation (-0.4 to -0.6). This is in contrast with the region semi-annual rain cycle which shows a weaker correlation (0.2 to 0.3).